Governance in genomics: a conceptual challenge for public health genomics law (Italian Journal of Public Health, 2006)
Increasing levels of genomic knowledge has led to awareness that new governance issues need to be takeninto consideration. While some countries have created new statutory laws in the last 10 years, sciencesupports the idea that genomic data should be treated like other medical data. In this article we discuss thethree core models of governance in medical law on a conceptual level. The three models, the Medical, PublicHealth and Fundamental Rights Model stress different values, or in legal terms serve different principles. TheMedical Model stands for expert knowledge and the standardisation of quality in healthcare. The PublicHealth Model fosters a social point of view as it advocates distribution justice in healthcare and anawareness of healthcare as a broader concept. The Fundamental Rights Model focuses on individual rightssuch as the right to privacy and autonomy. We argue that none of the models can be used in a purist fashionas governance in genomics should enable society and individuals to protect individual rights, to strive for adistribution justice and to ensure the quality of genomic services in one coherent process. Thus, genomicgovernance in genomics requires procedural law and a set of applicable principles. The principle whichunderlies all three models is the principle of medical beneficence. Therefore genomic governance shouldrefer to it as a key principle when conflicting rights of individuals or communities need to be balanced.
Keywords: genomics; models of governance; medical model; public health model; fundamental rights model; rules and principles; procedural law; indication; information justice